TOTAL QUALITY MANAGEMENT DAN KEPUASAN SISWA: STUDI EMPIRIS DI MTS AL-AMIRIYYAH BLOKAGUNG BANYUWANGI - Ali Amiruddin, Moh Sukron (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to analyze how the implementation of Total Quality Management (TQM) principles affects the level of student satisfaction at MTs Al-Amiriyyah Blokagung Banyuwangi. The focus of the study is on the implementation of TQM principles such as leadership commitment, involvement of all members of the madrasah, a culture of continuous improvement, and orientation towards customer satisfaction (students), as well as the extent to which the values of the pesantren and local culture strengthen the effectiveness of its implementation. The approach used is qualitative with a case study method. Data were collected through participatory observation, in-depth interviews with the head of the madrasah, teachers, and students, and documentation studies of the quality policies and managerial practices of the madrasah. Data analysis was carried out using the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. Triangulation of sources and methods was used to increase the validity of the findings. The results showed that the implementation of TQM at MTs Al-Amiriyyah has been running quite well, especially in terms of participatory leadership and teacher involvement. Student satisfaction is relatively high, especially in terms of religiosity and interaction with teachers. The findings also indicate that pesantren values such as sincerity, discipline, and manners towards teachers greatly support the success of TQM implementation. The implication of this study is the importance of integrating local values in the Islamic education quality management system, so that TQM is not only technical, but also contextual and sustainable.